Clinical and sociodemographic features in offspring aged 0–3 years of mothers with schizophrenia spectrum disorders. A descriptive cross‐sectional study - Edvardsen, Emilie; Moszkowicz, Mala; Olsen, Anne Lise; Heinrichsen, Michella; Pagsberg, Anne Katrine (Acta psychiatrica Scandinavica, 2024)
Objective Offspring of parents with schizophrenia spectrum disorders (SSD) have an increased risk of neurodevelopmental disturbances. However, the ability to provide very early interventions to support these children and their families requires profound knowledge regarding characteristic features of both the parents and their offspring. Information on this subject is currently sparse. The aim of the present study is to investigate clinical and sociodemographic variables in offspring in the age range of 0–3 years of mothers diagnosed with SSD. Methods The study is descriptive with a cross‐sectional design and includes parent‐child dyads consisting of mothers diagnosed with SSD (ICD‐10: F20‐29) and their offspring aged 0‐3 years, who were referred for examination and intervention at the infant and toddler psychiatric units, at the Mental Health Services, Capital Region, Copenhagen University Hospitals in two locations (Bispebjerg and Glostrup). Clinical and sociodemographic data were extracted from the Copenhagen “Infant Psychiatric Database” and processed by descriptive analysis. Results Out of 95 parent–child dyads considered for the study population, 85 were included. 27.8% of the mothers had psychiatric comorbidities, and 18.9% of the fathers had a psychiatric diagnosis at the time of investigation. Of the children, 89.7% were born full term (≥37th week) and most of them had a birth weight of ≥2500 g (81.8%). Of the mothers, 50% had experienced pregnancy complications of varying severity. Birth complications were seen in 62.9% of the dyads. Psychopathology was identified in 50% of the children at age 0–3 years, and 62.2% of the parent–child dyads appeared to have an affected relationship. Conclusion Results show widespread psychopathology in offspring aged 0–3 years of mothers with SSD. Moreover, several psychosocial stressors, clinical parental features, and relational disturbances are identified. These results contribute to a better understanding and identification of early risk markers of long‐term psychopathology in this infant patient group, and hence serve as potential targets for early interventions.